The Bergen Minke Whale in Naples – The scientific relationship between Wilhelm Frimann Koren Christie and the Italian natural scientist Stefano delle Chiaje - Torino, Marielva (Universitetet i Bergen, 2022)
In the Grand Hall of the Zoological Museum of Naples, a skeleton of a minke whale – a Balaenoptera rostrata – is exhibited. It is only recently that the history of this whale has been reconstructed. This was the result of research conducted in connection with an extensive biography of the Italian scientist and natural researcher Stefano delle Chiaje. The work revealed interesting documents in the State Archive of Naples and the Bergen Museum archive – documents that, when coupled together, supplement each other.